Cultural Dynamics and Islamic Legal Realities of Bundo Kanduang in the Patriarchal System of West Sumatra - Alikhsan, Rizky; Yenti, Endri (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
In the Minangkabau tradition, women hold a distinct society and cultural standing referred to as Bundo Kanduang, signifying their unique and esteemed position. This paper aims to examine the position upheld by ethnic Minangkabau women within patriarchy framework of the customary law of West Sumatra and the general Islamic law. This study is qualitative and was conducted using a comparative law approach. To achieve the study aim, data were obtained from interviews with academics, cultural and religious leaders, as well as tradition leaders. The obtained results showed a decline in the status of Bundo Kanduang within the Minangkabau customs. In this custom, the glory of women holding heirloom property was only being used as a symbol. Meanwhile, Islamic law acknowledges that granting rights to women is not contradictory or incompatible. Typically, Islam creates room for equality in the roles and functions of women and men within the Minangkabau community, allowing women (Bundo Kanduang), to have equal opportunities in the public sphere, particularly in the field of work. Based on this understanding, it is crucial to deeply instill in the younger generation an understanding of their position within the customs, religious values, family dynamics, and cultural heritage. This comprehensive education is particularly important as it ensures their awareness of functions and positions, aiming to prevent cultural disparities within the Minangkabau society.